A case of parathyroid carcinoma: the rarest endocrine cancer (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Parathyroid neoplasm is the rarest endocrine cancer and an infrequent cause of primary hyperparathyroidism, responsible for less than 1% of cases. A 32-year-old male presented with neck swelling, generalized body aches, pain in multiple joints, and weight loss. When USG found a solid nodule in the left lobe, he underwent left hemithyroidectomy with excision of the left superior parathyroid mass but parathyroid and calcium level was persistently elevated and a whole-body scan suggested metastatic bone diseases. Finally, the completion thyroidectomy and excision of the remaining parathyroid mass were done successfully. One month after surgery patient became hypothyroid while parathyroid hormone and calcium came back to normal. He was diagnosed as a case of primary hyperparathyroidism due to parathyroid carcinoma with bone metastasis.J Assoc Clin Endocrinol Diabetol Bangladesh, July 2022; 1 (2): 65-68